Triggering effect caused by elemental sulfur as a mean to reduce the polymerization temperature of benzoxazine monomers - Rodriguez Arza, Carlos (2016)
Mixtures of different benzoxazine resins and elemental sulfur (S8) are prepared and then reacted at 120 °C, below the temperature for radical formation of sulfur. The progress of the reaction and the chemical structures of the main products are monitored and characterized by proton nuclear magnetic resonance spectroscopy (1H NMR) and Fourier transform infrared spectroscopy (FT-IR). Thermal analysis of all reactive systems are also performed and studied by differential scanning calorimetry (DSC). The introduction of S8 into benzoxazines generates a new structure bearing a Schiff base and a phenolic -OH within the reactive system, which then triggers the reduction of the polymerization temperature in about 15% when as low as 5 mol% of S8 is added.